Can the Choice of Cementless Implants and Bearings during Total Hip Arthroplasty Have an Impact on the Overall Costs within a Bundled Payment Model? - Duncan, Stephen; Patel, Ankur; Delhougne, Gary; Patrick, Corey (The Journal of Hip Surgery, 2020)
The comprehensive care for joint replacement model from the Center for Medicare and Medicaid Services and similar programs from other payers make hospitals and health care systems more responsible for better clinical and economic outcomes of total hip arthroplasty (THA) patients. The objective of the study was to evaluate hospital-related clinical and economic outcomes of using the cementless R3 cup and Polarstem with an oxidized zirconium bearing compared with other cementless hip systems using a ceramic bearing in THA patients. We retrospectively reviewed primary THA patients from the premier perspective database between 2014 and 2018Q3. Patients with R3 cup and Polarstem with an oxidized zirconium bearing were identified using appropriate keywords from billing records and compared against cementless and ceramic-on-polyethylene (CoP) THA patients who did not meet the keywords' criteria. Patients were excluded if they were < 21 years of age; outpatient hospital discharges; evidence of revision THA; bilateral THA in same discharge or different discharges. 1:3 propensity score matching was used to control patients' demographic, clinical, and hospital characteristics. Generalized estimating equation model with appropriate distribution and link function was used to estimate hospital-related cost while logistic regression models were used to estimate discharged status, transfusion, and 30-days readmission. The study matched 818 R3/Polarstem with oxidized zirconium bearing patients with 2,454 CoP cementless THA patients. Length of stay for the R3/Polarstem patients (mean = 1.61 days; confidence interval [CI] = 1.41–1.80) was significantly lower (p-value ≤ 0.0001) than CoP THA patients (mean = 2.06 days; CI = 1.95–2.17). R3/Polarstem hip patients were 36% (odds ratio [OR] = 1.36; CI = 1.07–1.72; p-value = 0.0112) more likely to be discharged to home/home health care, 18% (OR = 0.82; CI = 0.63–1.06; p-value = 0.1235) less likely to be discharged to a skilled nursing facility (SNF), 84% less likely to have transfusion (OR = 0.16; CI = 0.09–0.29; p-value ≤ 0.0001), and 44% (OR = 0.56; CI = 0.32–0.98; p-value = 0.0412) less likely to readmitted within 30 days than CoP THA patients. Mean total hospital costs was marginally higher for R3/Polarstem patients (mean = $15,611; vs. $15,002; p-value = 0.0041) than CoP THA patients. While the total hospital costs for the R3/Polarstem was higher than CoP, the reduced length of stay, reduced discharge to SNF, and lower readmission rates can help to save money in the bundled payment and make the use of certain cementless hip systems a potential cost saving solution.
Keywords: oxidized zirconium hip implant; length of stay; discharge status; total hospital cost